The Histone Variant H3.3 Is Enriched at Drosophila Amplicon Origins but Does Not Mark Them for Activation. Issue 6 (1st June 2016) - Paranjape, Neha P; Calvi, Brian R
Abstract: Eukaryotic DNA replication begins from multiple origins. The origin recognition complex (ORC) binds origin DNA and scaffolds assembly of a prereplicative complex (pre-RC), which is subsequently activated to initiate DNA replication. In multicellular eukaryotes, origins do not share a strict DNA consensus sequence, and their activity changes in concert with chromatin status during development, but mechanisms are ill-defined. Previous genome-wide analyses in Drosophila and other organisms have revealed a correlation between ORC binding sites and the histone variant H3.3. This correlation suggests that H3.3 may designate origin sites, but this idea has remained untested. To address this question, we examined the enrichment and function of H3.3 at the origins responsible for developmental gene amplification in the somatic follicle cells of the Drosophila ovary. We found that H3.3 is abundant at these amplicon origins. H3.3 levels remained high when replication initiation was blocked, indicating that H3.3 is abundant at the origins before activation of the pre-RC. H3.3 was also enriched at the origins during early oogenesis, raising the possibility that H3.3 bookmarks sites for later amplification. However, flies null mutant for both of the H3.3 genes in Drosophila did not have overt defects in developmental gene amplification or genomic replication, suggesting that H3.3 is not essential for the assembly or activation of the pre-RC at origins. Instead, our results imply that the correlation between H3.3 and ORC sites reflects other chromatin attributes that are important for origin function.